The impact of supply phase shift on the three phase induction motor operation - Adekitan, Aderibigbe (Array, 2019)
The performance of a three-phase induction motor operating under supply unbalance conditions has been the focus of many research works using various methods. Most of the studies have focused majorly on voltage magnitude unbalance without due analysis to determine the effect of deviations in the supply phase angle from the 120° phase to phase displacement. This research investigates the significance of supply phase shift on the performance of a three-phase induction motor by applying a novel phase shift unbalance definition to the zero, negative and positive sequence components model of the motor. The test results reveal that when both phase angle shift and voltage magnitude unbalance occur simultaneously during motor operation the effect of the phase shift dominates over the effects of the voltage magnitude unbalance. This study shows that phase angle unbalance has a severe consequence on three phase motor performance.